Spatial analysis of the phenomenon of dropout of primary school students in the city of Baghdad for the year 2009/2010 / - Eyal, Shaker Mahmoud; Sajit, Ali Abdul Amir (Al-Adab Journal, 2015)
This study deals with dropout of pupils in primary education in Baghdad in 2009 /2010 in terms of geography, and fall within the population studies, where the dropout one of the factors influencing the educational structure of the population. The study shows that dropouts’ pupils in primary schools in Baghdad distributed uneven geographical distribution, and Baghdad city considers the most dropouts of pupils at this level of learning. The percentage of dropout pupils was (19.4%) of the total dropouts in Iraq, and at the municipal level in the city. It is observed that there is a disparity in dropout rates from one municipality to another, where learning area topped in Baghdad Al-Jadida municipality for dropout pupils, and the proportional importance was (17.1%) of the total dropouts in Baghdad city, While dropout rates fell to the lowest level in the municipality of Al-Mansour, and the proportional importance was (1.1%) of the total dropouts in the city. The dropout by type has also varied according to the geographical distribution in the city of Baghdad and by municipalities, the percentage of dropout male pupils was (55.6%), versus (44.4%) for females, Baghdad Al-Jadida municipality came as the highest percentage of dropout male pupils with (18.7%) percentage, while Mansour municipality was less proportions of dropout male pupils, the proportional importance was (1.1%) of the total male dropouts in the city of Baghdad, of the total male dropouts in the city of Baghdad, while the highest percentage of female dropout pupils was in Al-Sader AL- oula municipality with percentage (17.6%), While the municipality of Al-adhamiya was the least and the proportional importance was (1%) of the total dropouts in the city of Baghdad. On grade level, it had to be identified the dropout of the importance of variability detected at the level of the classroom also. At the city level, the highest percentage of dropout was in the fifth grade valued (22.7%) of the total dropouts in the city of Baghdad. the image of the geographical distribution of dropout varied by the classroom between municipalities in the city of Baghdad, while the dropout was in the fifth grade in the Al-Karkh municipality with ​​(32.3%) percentage as the highest rate of dropout between municipalities, Al-Doraa municipality was the lowest dropout rate for the second grade with (8.6%) percentage of the total dropouts in the municipality itself. To detect the affecting factors of the variation to this phenomenon and a spatial analysis of this discrepancy, it has been studied of spatial relations with a number of variables. And through the study, it shows that there is a spatial variation of the spatial relationships between the pupils’ dropout in primary stage in Baghdad and related variables. At the city level, a two-way relationship emerged, proportional trend was (age structure of the drop-outs) variable, the strongest relationship in the dropout, the reverse trend was for (services provided by the school to pupils) variable, the strongest impact in the dropout. At the municipal level, the relationship was proportional with (age structure of the drop-outs) variable, which is the most influential phenomenon in most municipalities. Followed by (the parent who lives with him leaking) variable in Al-Rasheed municipality, while inverse relationship appeared as the most influential on school dropout with (monthly income of the family) variable in the Al-Ghadeer municipality.